Comparison of body image dissatisfaction among adolescent boys who do and do not stutter and investigating the relationship between body image dissatisfaction, anxiety and Self-assessed stuttering severity - Mahsa Taherifard; Leila Ghahremani; Zahra Gheibi; Mohsen Saeidmanesh; Maryam Vahab (BMC Psychology)
Abstract Background Dissatisfaction with body image in adolescents may be associated with disorders such as anxiety. As studies have reported a high risk of anxiety disorders, especially social anxiety, in people who stutter, the present study aimed to compare body image dissatisfaction in adolescent boys who do and do not stutter and investigate the association between body image dissatisfaction and anxiety in both groups. Materials and methods This is a cross-sectional study in which 102 adolescent male students aged 15 to 17 years (divided into two groups: 51 who stutter and 51 who do not stutter) completed the questionnaires that included an informed consent form, a body image satisfaction scale, an anxiety scale, and a self-assessed stuttering severity scale. Results According to the results, 55% of adolescent boys who stutter had high levels of obsessive-compulsive disorder (OCD), and 59% of them had high levels of generalized anxiety disorder (GAD), while in adolescent boys who do not stutter these percentages were 43% for OCD and 49% for GAD. In addition, adolescents who stuttered were found to be significantly more dissatisfied with their faces. The path analysis model also revealed a positive relationship between self-assessed stuttering severity and dissatisfaction with body image due to anxiety. In addition, the results showed that in both groups there was a positive correlation between the values of all anxiety subscales and dissatisfaction with body image. Conclusion A significant positive correlation was found between self-assessed stuttering severity, anxiety (particularly social anxiety), and body image dissatisfaction in adolescent boys. Therefore, the measurement of anxiety and body image dissatisfaction seems to be of particular importance in adolescent boys with moderate to high self-assessed stuttering severity.